Republic of Korea : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2009)
This Selected Issues paper evaluates the size of fiscal multipliers in Korea using the IMF's Global Integrated Monetary and Fiscal model calibrated for Korea. The sensitivity of the results to a number of key factors is explored. Based on this, the impact of the recent fiscal stimulus packages is estimated and the appropriateness of the current mix of measures is assessed. In this context, the paper also draws on international operational experience with fiscal stimulus measures.